Estudio del Patrimonio Cultural Inmaterial del ámbito tradiciones y expresiones orales, subámbito leyendas y expresiones orales para la creación de una guía, en la parroquia Aan Juan de Pastocalle, cantón Latacunga, provincia de Cotopaxi - Llano Viracocha, Irma Nataly (2017)
The loss of ancestral knowledge is a problem that has deepen in the last years. Being the legends one that is almost lost due to the lack of transmission of that particular knowledge from generation to generation. This project is carried out in San Juan de Pastocalle parish with a population of 1.449 (INEN, 2010). Considered as an areas with a variety of natural and cultural resources. In this case, the research focused on the intangible cultural resources, that according to the classification of the National Institute of Cultural Heritage (INPC for its acronym in Spanish) it is subdivided into areas and sub areas, being in this case the area oral traditions and expressions and the sub area legends and oral expressions. Those were rescued from collective memories that the elders of the community had. The first step for this research was to stablish the situation diagnosis, which was done through the gathering of primary and secondary information and data collection. That allowed to stablish the main issues that concerns the parish among them was the loss of cultural identity, the loss of ancestral knowledge due to migration and acculturation. To carry out the inventory of cultural resources the INPC tabs were applied, focused only on the particular subarea concerning this research. 12 legends were identified and inventoried which were framed in religious, supernatural, toponymy and anthroponomy. Most of them has a medium sensitivity of change, which means that they are vulnerable since they are not frequently narrated and the existing population who know about them is reduced. As part of the research a guide was designed which could be an instrument to keep those legends and to extend its knowledge to the society to be spread subsequently. It is suggested to continue the study of cultural patrimony due to their importance for the society to stop them being threatened by the changes of the social dynamics.